EFEKTIFITAS MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) DALAM MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA DI SEKOLAH DASAR - Saidatul Irfana; Syailin Nichla Choirin Attalina; Aan Widiyono (LPPM Universitas Bina Bangsa, 2022)
This research is motivated by the learning problems that were previously carried out face-to-face now turned into online learning (in the network). This causes a decrease in student interest and learning outcomes while participating in online learning. The low learning outcomes are evidenced by the acquisition of an average grade of 30 students in grade 4, there are 47% of students whose scores reach the KKM and 53% of students whose scores do not reach the KKM 75. Based on this research, it is hoped that the application of the Project Based Learning (PjBL) learning model is effective in improving interest and student learning outcomes. This study uses a quantitative research approach with an intact-group comparison design experimental method. This study used a questionnaire and test data collection instruments. Then the data were analyzed using the Independent Sample t-test. Based on the results of the t-test obtained tcount> ttable, namely 15,878 > 1,688 and the results of the t test on the learning outcome variables show that tcount> t table, 6,964 > 1,688. It can be concluded that the Project Based Learning (PjBL) learning model is effective in increasing the interest and learning outcomes